NILAI-NILAI TARI INDANG TAGAK DALAM SOSIAL MASYARAKAT JORONG SAMPU NAGARI LUBUK GADANG UTARA KECAMATAN SANGIR KABUPATEN SOLOK SELATAN: KAJIAN ASPEK WAKTU - Agestia, Feby; Desfiarni, Desfiarni (SENDRATASIK UNP, 2019)
AbstractÂ This research aims to reveal and describe the values of Indang Tagak dance in Jorong Sampu Nagari Lubuk Gadang Utara Sangir District, South Solok Regency: Analysis of Time Aspects ". This research was a qualitative research that produced descriptive analysis data. The main instrument of this research was the research herself and assisted by supporting instruments such as stationeries and cameras. The techniques of data collection were carried out by means of literature study, observation, interviews and documentation. The steps for analyzing data were collecting data, describing data and making conclusions. The results confirmed that the social values contained in the Indang Tagak Dance which were material, vital and spiritual values of the Indang Tagak Dance were useful for humans. Indang Tagak Dance is a folk art group in Jorong Sampu Nagari Lubuk Gadang Utara which is always performed during traditional ceremonies for the celebration of Muslim days. The creation of Indang Tagak Dance tells the history of spreading Islam, its movements and songs have meaning about the basics of teachings of Islam.Â Keywords: Indang Tagak dance values, time aspect review